Change and instability in area and production of wheat and maize in Bangladesh (Bangladesh Journal of Agricultural Research, 2008)
The study measured the change and instability in area, production, and yield of two major cereal crops wheat and maize in Bangladesh based on secondary data during 1980/81-2003/04 using different statistical techniques. Area and production of wheat increased satisfactorily. But yield was not increased to meet the demand of the country. In the case of maize, significant increment happened in yield during the study period. Area and production of maize also increased to fulfill the increasing demand of population. Presently production of maize increased more rapidly than its area. The growth in area, production, and yield of wheat slightly improved in period-II, whereas the growth rate in area, production, and yield of maize improved rapidly. Though both of wheat and maize are unstable crops, maize showed very instability in its area and production because of its increasing tendency in the recent years. Key Words: Change and instability, production, wheat, maize. doi:10.3329/bjar.v33i3.1600 Bangladesh J. Agril. Res. 33(3) : 409-417, September 2008